PENERJEMAHAN MODALITAS IRAI PADA KOMIK ONE PIECE - Febriana, Nanda; Aibonotika, Arza; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study examines the equivalence of irai modalities in Japanese One Piece comics and Indonesian One Piece comics. The purpose of this research is to explore the correspondence form and equivalent meaning of irai modality in One Piece comic. This study uses the Newmark (1988) translation procedure as a reference to identify the translation techniques that is being used. The classification of Indonesian modalities by Alwi (1992) is used to reference Indonesian modalities while for irregular modalities the irrigation classifications are used by Nitta. The method used in this study is descriptive analysis method. The data used came from Japanese One Piece comics volumes 1,2,3 and 4. It has been found that there were 51 forms of irai modality in total. Those forms are shite, te kure, te kudasai, te hoshii, te kureruka, and te kurenaika. Based on the data, the modality markers of the form of te te, shite, kudasai, kureruka and kurenaika have the meaning of requests to do, whereas the markers of form te te hoshi have the meaning of a statement of desire.Key Words: Translation, Modality, Comic, Equivalent Meaning